Inter-Rater Reliability among Dentists for Assessment of Depth of Impacted Third Molars on Orthopantomograms - Fatima Liaqat, Areej Gakhar, Ziyab Wajid Siddiqui, Maria Jabbar, Saman Fatima, Hira Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the inter-rater reliability of dentists regarding assessment of depth of impacted third molars on the Orthopantomograms Methods: A cross sectional comparative study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore in which dentists from four different specialties namely; Oral Pathology, Endodontics, Prosthodontics and Oral and Maxillofacial surgery were included as raters. The study was conducted from December 2020 to February 2021. A total of 21 Orthopantomograms were assigned to each rater for assessing the angle of the impacted third molar. The classification for angle of impaction used was Winter`s classificati1. The raters were provided with the OPGs and a proforma for recording their observations. Results: The level of agreement regarding the depth of impacted third molars observed on the Orthopantomograms between rater 1 with rater 2 (κ=.692, p≤0.001) and rater 1 with rater 3 (κ=.639, p≤0.001) was very strong but was moderate with rater 4 (κ=.538, p=0.001). Conclusion: There was an excellent agreement regarding the depth of impacted third molars of rater 1 (Oral and maxillofacial surgeon) with rater 2 (oral pathologist) and rater 3 (Prosthodontist) but a moderate agreement with rater 4 (Endodontist). Keywords: Depth of impaction, Third molars, Inter-rater reliability, Orthopantomograms